Effective Air Purification via Pt-Decorated N3-CNT Adsorbent - Yang, Yinli; Liu, Sitong; Guo, Kai; Chen, Liang; Xu, Jing; Liu, Wei (Frontiers in Ecology and Evolution, 2022)
Effectively removal of air pollutants using adsorbents is one of the most important methods to purify the air. In this work, we proposed for the first time that PtN3-CNT is an effective adsorbent for air purification. Its air purification performance was studied by calculating the adsorption behaviors and electronic structures of 12 gas molecules, including the main components of air (N2, O2, H2O, CO2) and the most common air pollutants (NO, NO2, SO3, SO2, CO, O3, NH3, H2S), on the surface of PtN3-CNT using first-principles calculations. The results showed that these gases were adsorbed stably via the coordination between Pt and the coordinated atoms (C, N, O and S atoms) in the gas molecules, and the adsorption energies vary in the range of -0.81~-4.28 eV. The obvious chemical interactions between PtN3-CNT and the adsorbed gas molecules are mainly determined by the apparent overlaps between the Pt 5d orbitals and the outmost p orbitals of the coordination atoms. PtN3-CNT has strong adsorption capacity for the toxic gas molecules, while relatively weaker adsorption performance for the main components of the air except oxygen. The recovery time of each adsorbed molecule calculated at different temperatures showed that, CO2, H2O and N2 can be desorbed gradually at 298~498K, while the toxic gases are always adsorbed stably on the surface of PtN3-CNT. Considering the excellent thermal stability of PtN3-CNT at up to 1000 K proved by AIMD, PtN3-CNT is very suitable to act as an adsorbent to remove toxic gases to achieve the purpose of air purification. Our findings in this report would be beneficial for exploiting possible carbon-based air purification adsorbents with excellent adsorbing ability and good recovery performance.